Perancangan dan Pengembangan Sistem Manajemen Karyawan pada PT Asta Satria Investama - Suwarno Suwarno; William Surya Jaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The utilization of information technology in the operational activities of a company has ensured the company's high performance. One of the examples was the design and development of an employee management system. This article describes the implementation of Job Training (KP) at a game development company in Batam City, named PT Asta Satria Investama. The development of an employee management system application is required because the data recording activities, attendance control, and employee leave requests are still done manually. The author uses data collection methods in the form of observations and interviews, as well as iterations that are carried out in stages while in the development process. The output of this activity will be implemented and used by HR department at PT Asta Satria Investama